Determination of Zinc & Iron Concentrations in Different Types of Dates & Vegetables in Baghdad - S. M. Murbat Al-Jobori (Journal of Madenat Alelem University College, 2015)
The aim of the present study is to determine the concentration of zinc & iron in dates & vegetables and compare the results with other foods. The present study conclude that the concentration of Fe & Zinc of some selected samples of Iraqi dates and vegetables were higher than all previous works done on Iraqi vegetables, & within the safe limits for Iron (Fe) and Zinc (Zn), respectively set by the WHO/FAO. The present study recommends that pregnant & lactating women should encourage to take dates for at least twice a day. Also, Trace & major elements in vegetables & fruit in Baghdad city should be measured.